2011
DOI: 10.1159/000331857
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Lymphocytes, Thyrocytes and Fibroblasts in Hashimoto’s Thyroiditis: An Immunohistochemical and Ultrastructural Study

Abstract: Background: The mechanism of autoimmune reaction, a diffuse process consisting of a combination of epithelial cell destruction, lymphoid cellular infiltration, and fibrosis in Hashimoto’s thyroiditis, is not well known. The aim of this study was to analyse the cell subsets in thyroid tissue of patients with Hashimoto’s thyroiditis. Methods: We studied paraffin-embedded thyroid specimens obtained from children with Hashimoto’s thyroiditis and children without an autoimmune thyroid disease. Mononuclear T cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
1
15
1
5
Order By: Relevance
“…), as they comprised point‐to‐point contacts between cell membranes, without the underlying cell structures that are observed in the other types of junctions. The ultrastructure of these contacts was comparable with that of immunological synapses (between immunological cells and other cell types), and to our knowledge such contacts formed by tumour cells have not been reported previously. Many studies have reported on the potential of stromal cells to induce tumour growth in PCa .…”
Section: Discussionsupporting
confidence: 81%
“…), as they comprised point‐to‐point contacts between cell membranes, without the underlying cell structures that are observed in the other types of junctions. The ultrastructure of these contacts was comparable with that of immunological synapses (between immunological cells and other cell types), and to our knowledge such contacts formed by tumour cells have not been reported previously. Many studies have reported on the potential of stromal cells to induce tumour growth in PCa .…”
Section: Discussionsupporting
confidence: 81%
“…Our results demonstrated a significant increase of CD28-negative T cells in HT patients, associated with CMV-seropositivity within the CD8+ T cell subpopulation. A role of CD8+ T cells in thyroid inflammation, particularly in HT, was also clearly shown by others [15,26-28]. Our results on CD28 expression differ from a study in 35 children with autoimmune thyroiditis in whom baseline CD28 expression was similar to healthy controls [29].…”
Section: Discussioncontrasting
confidence: 63%
“… 1 The main features of Hashimoto’s thyroiditis include increased serum thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TGAb), and infiltration of lymphocytes and plasma cells into the thyroid. 2 5 In urban areas of China, the prevalence of TPOAb positive and TGAb positive were 11.5% and 12.6%, respectively. 6 Hashimoto’s thyroiditis can also cause primary hypothyroidism, thyroid cancer, atherosclerosis, diabetes, and adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%